STEM-Based Teaching Module with a Realistic Mathematics Education Approach to Improve Critical Thinking Skills among Vocational High School Students in an Automotive Engineering Program - Kadir Alpan Alaydrus; Sutarto Sutarto; Saiful Prayogi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aimed to examine the effectiveness of a STEM-based teaching module with a Realistic Mathematics Education (RME) approach in improving the critical thinking skills of vocational high school students in the Automotive Engineering Expertise Program. The study employed a mixed-methods approach with an explanatory sequential design. The quantitative phase was conducted through a quasi-experiment using a pretest-posttest control group design, while the qualitative phase was conducted through semi-structured interviews with mathematics teachers. The participants were 62 eleventh-grade Motorcycle Engineering students at SMK Negeri 1 Pringgabaya, consisting of 31 students in the experimental group and 31 students in the control group. The experimental group received instruction using the STEM-RME-based teaching module, whereas the control group received expository instruction. The quantitative instrument was a written test consisting of 15 multiple-choice items and 5 open-ended questions. The data were analyzed using descriptive statistics, gain scores, N-Gain, paired-samples t-test, independent-samples t-test, mixed-design ANOVA, and thematic analysis. The results showed that the mean score of the experimental group increased from 22.39 to 28.97, while that of the control group increased from 22.23 to 24.87. The mean N-Gain of the experimental group was 0.53, categorized as moderate, whereas that of the control group was 0.20, categorized as low. The paired-samples t-test showed a significant improvement in the experimental group, t(30) = 27.95, p < 0.001, and in the control group, t(30) = 7.52, p < 0.001. The independent-samples t-test showed significant differences in the posttest score, t(56.81) = 11.20, p < 0.001, gain score, t(60) = 9.30, p < 0.001, and N-Gain, t(60) = 9.64, p < 0.001. The mixed-design ANOVA revealed a significant time × group interaction, F(1,60) = 86.43, p < 0.001. The teacher interview findings indicated that students found it easier to understand mathematical concepts when the material was connected to automotive contexts, such as wheels, tires, rims, disc brakes, gears, sprockets, pulleys, and tangent lines on vehicle components. The teachers also emphasized that real-life contexts, teaching aids, modeling, discussion, and visualization helped students overcome difficulties in visualizing geometry and encouraged them to provide reasoning and check the reasonableness of their answers. Thus, the STEM-RME-based teaching module was effective in improving students’ critical thinking skills.